Original articleSubdural infusion of dexamethasone inhibits leukomyelitis after acute spinal cord injury in a rat model - Kwiecien, Jacek M.; Jarosz, Bozena; Urdzikova, Lucia Machova; Rola, Radoslaw; Dabrowski, Wojciech (Folia Neuropathologica, 2015)
Trauma in spinal cord injury often results in massive damage to the white matter and in damage to myelin that results in a severe phagocyte-rich infiltration apparently directed at removing immunologically toxic myelin debris. In the epidural balloon crush injury to the rat cranial thoracic spinal cord, the dorsal column was crushed, which at one week post-op resulted in its obliteration by a severe infiltration by a virtually pure population of macrophages that internalized all damaged myelin. A week-long subdural infusion of dexamethasone, a stable synthetic corticosteroid, resulted in remarkable inhibition of the macrophage infiltration of the crush cavity and in the lack of removal of myelin debris by phagocytosis. In this study we demonstrated that spinal cord injury results in a severe inflammatory response directed at massively damaged myelin, and we inhibited this response with a subdural infusion of a powerful anti-inflammatory drug, dexamethasone.